Anticoagulation therapy in haemophilia - Schutgens, R.E.G.; Tuinenburg, A.; Fischer, K.; Mauser-Bunschoten, E. P. (Hämostaseologie, 2013)
Patients with haemophilia (PWH) are relatively protected from cardiovascular death. Recent insights have shown that this is not due to less formation of atherosclerosis than in non-haemophilic men, therefore protection from the final occlusive thrombus will be the major determinant. Prevalence and incidence rates of cardiovascular disease (especially non-fatal events) are scarce, although ongoing studies are addressing this issue.Meanwhile, because the haemophilia population is aging, we are increasingly confronted with cardiovascular events. The main cardio vascular risk factors that should be part of regular screening programs are hypertension, overweight, lipometabolic disorders and smoking. Anticoagulation therapy in haemophilia is feasible, provided that individual tailored coagulation therapy and close monitoring is provided.Here, we present our view on anticoagulation management in PWH. There is an absolute need for risk assessment tools and prospective validation of suggested anticoagulation management strategies in PWH. Until then, we are managing the unknown.
Keywords: Haemophilia; anticoagulation; aspirin; coumarin; cardiovascular disease; atrial fibrillation